Patient Relationship Management: Emerging EDGE in Medical: Enhancing Patient Satisfaction through Relationship Management (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Patient relationship management shows the hospitals version of customer relationship management. Patients are active customers in this modern era. This is the reason patients have been part of the opportunities for the hospitals to attract prospective patients and retaining the existing patients. The paper basically focuses on increasing the patient satisfaction while using various practices by the hospitals. Each area has its own drawbacks, the concept is not popular in the rural areas.